Optimization of electrode shape for high power GaN-based light-emitting diodes - 范玉佩 程立文 林岳明 张俊兵 曾祥华 (Optoelectronics letters, 2009)
Because the polarization effect influences the distribution of the carriers in the multiple quantum wells of the light-emitting diodes （LEDs）, the light-emitting efficiency is also affected. The influence of the polarization effect on GaN-based LEDs＇ performance is simulated. By simulating four different types of electrode shapes, it＇s found that the electrode shape influences not only the photoelectric characteristics but also the optical absorption by the semiconductor. Through the optimization of the electrode shape, the I-V characteristic is improved, and the series resistance is lowered. The optical absorption by the semiconductor is decreased and then the heat generated in the LEDs is lowered. As a result, both the photoelectric conversion efficiency and the stability are improved.